Efficacy and Safety of Fentanyl as An Adjuvant with Bupivacaine and Lignocaine in Supraclavicular Brachial Plexus Block (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Adding narcotics to local anesthetic is very effective in prolonging the analgesic effects. The aim of this study is to evaluation the efficacy and safety of fentanyl as an adjuvant with bupivacaine-lignocaine in supraclavicular block.Methods: This analytical study was carried out in the department of anesthesiology in Chittagong Medical College Hospital in collaboration with the department of orthopedic surgery over a period of 22 months starting from January 2012 to December 2014. A total 130 adult patients of either sex with American Society of Anesthesiology (ASA) health status I-II were selected for upper limb surgery under supraclavicular brachial plexus block was randomly allocated in to two groups of 65 patients in each. Group- C was received Distilled water 2ml and Group-F was received fentanyl 2ml (100 g) in 38ml of bupivacaine and lignocaine with adrenaline (Total volume of 40ml).Results: The mean onset of sensory & motor block was 10.49±0.75 min & 9.41±0.76 min in group-C and 7.60±3.711min & 9.23±5.114min in group-F. The duration of analgesia in group-C was 3.81±0.88 hrs and in group-F was 8.62±1.747 hrs.Conclusion: There was significantly prolonged duration of analgesia and better onset of sensory and motor block in fentanyl group without any unwanted effects.Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 31-35